Examining spectral converters for emerging photovoltaic technologies - MCKENNA, BARRY (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Spectral converters are photoluminescent layers which can selectively absorb solar photons of wavelengths which are not efficiently converted to electricity by a photovoltaic (PV) cell, and re-emit these photons at wavelengths more suitable for use. These materials are attractive for complementary application with PV devices due to the versatility afforded to them by the choice of luminophore which can be tuned to the PV cell in question. The ability of these materials to harvest ultraviolet (UV) radiation and emit it at longer, less harmful wavelengths means they can potentially improve the photostability of emerging PV technologies, in particular, perovskite solar cells (PSCs). PSCs are limited currently by their instability to moisture, which when present in conjunction with light and heat can cause irreversible degradation. In order to address the current limitations of PSCs, the first part of this work will investigate a two-fold approach of both polymer encapsulation to improve the resistance of the device to moisture-induced degradation (Chapter 3) and the addition of luminescent down-shifting (LDS) layers to act as UV-filters (Chapter 4). To investigate the requirements of an encapsulant for PSCs, bare perovskite layers were thermally degraded with and without polymer encapsulation. This degradation was monitored by X-ray diffraction, UV/Vis absorption spectroscopy and epi-fluorescence microscopy. It was found that the water vapour transport rate within the polymer had the greatest impact on its ability to act as an encapsulant for PSCs. Poly(methyl methacrylate) (PMMA) performed the best, with stabilities of over 400 h achieved for elevated temperatures (60 ?C) and thus, was used as the host material for the LDS layers coated on the PSCs in Chapter 4. LDS coatings applied to CH3NH3PbI3 PSCs using the luminophores Lumogen F Violet 570, polyfluorene and 2-(2-hydroxyphenyl)quinazolin-4(3H)-one exhibited enhanced power conversion efficiencies (PCE) and external quantum efficiencies (EQE). The device photostability, however, was not measurably enhanced upon coating due to device degradation caused by alternative degradation pathways (thermal, moisture) occurring on a faster timescale. The use of nanocrystals for spectral converters was then investigated. The tunable emission properties of CH3NH3PbBr3-xIx mixed-halide perovskite nanocrystals (PNCs) upon dilution was examined in Chapter 5. It was determined by photoluminescence spectroscopy and transmission electron microscopy that a red-shift in PNC emission occurred due to aggregation and uncontrolled growth of the PNCs caused by decreasing capping ligand concentration in solution. This growth led to particles with dimensions ca. 1 ?m and the uptake of the excess iodide bound within the capping ligands. This red-shift occurs independently of the makeup of the precursor solution and is directly related to the iodide content and anti-solvent utilised. Finally, due to the issues with the solution phase instability of PNCs, in Chapter 6 CdSe@ZnS/ZnS QDs were investigated as luminophores for large-area luminescent solar concentrators (LSCs). Due to the inhomogeneity of the edge emission observed for these LSCs, a detailed study into the optical characterisation protocols for large planar LSCs was undertaken. It was found that determining the mean edge emission from multiple overlapping intervals is the most accurate characterisation method. The LSCs were coupled with a thin strip DSSC and a photocurrent was obtained. These examples illustrate the versatility of spectral converters and highlight the range of applications they can be used for with emerging PV technologies. The stability and efficiency of PV cells can be improved, the materials required can be minimised and the optical properties of our conversion techniques can be carefully tuned for the application and device architecture required.
APPROVED
Keywords: solar; perovskite; nanocrystal; photovoltaic; luminescent